Playability Evaluation using the Heuristic Evaluation of Playability Method in Warcraft 3 Reforged - Aldhiqo Yusron Mubarok; Umi Chotijah (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
Game is a digital activity that is very popular in the modern era, both among young and old. One game that is very popular with E-sports competition is Warcraft 3. However, in 2020 it immediately fell because Blizzard company has released a new version of those games which is called warcraft 3 reforged. The purpose of this study was to find out the reason this could happen by using the heuristic evaluation of playability method. With this method, you can find the scale of the problem in a game that will be released. The data used for this study uses the player persona as the source of the assessment that will be carried out in this game. The player persona is created by providing 10 respondents who will be required to perform and assess each task given according to the scenario codes. The benefits of this research can be used to analyse the readiness of games to be released to the market and to find out customer tastes in RTS (Real Time Strategy) type games. This assessment is based on the mean rating which will later be categorized as the level of problem in the running of the game. The results of this study indicate that the mean rating in this game is 2.91 or can be referred to as the Major Usability Problem with the highest value of percentage with the highest problem category found in the game usability with a percentage value of 41.7%.